2017
DOI: 10.3390/insects8040116
|View full text |Cite
|
Sign up to set email alerts
|

To Spray or Not to Spray: A Decision Analysis of Coffee Berry Borer in Hawaii

Abstract: Integrated pest management strategies were adopted to combat the coffee berry borer (CBB) after its arrival in Hawaii in 2010. A decision tree framework is used to model the CBB integrated pest management recommendations, for potential use by growers and to assist in developing and evaluating management strategies and policies. The model focuses on pesticide spraying (spray/no spray) as the most significant pest management decision within each period over the entire crop season. The main result from the analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Degree-day accumulation would then be re-started to predict emergence of the third generation and so on. This strategy has the advantage of controlling CBB populations early in the growing season, which has been shown to be critical for minimizing crop damage for the remainder of the season [19]. This two-phase method will also help reduce pesticide inputs into the environment, as well as lower labor and production costs for the grower as pesticides will only need to be applied at certain points in the year rather than using regularly scheduled calendar sprays [17, 19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Degree-day accumulation would then be re-started to predict emergence of the third generation and so on. This strategy has the advantage of controlling CBB populations early in the growing season, which has been shown to be critical for minimizing crop damage for the remainder of the season [19]. This two-phase method will also help reduce pesticide inputs into the environment, as well as lower labor and production costs for the grower as pesticides will only need to be applied at certain points in the year rather than using regularly scheduled calendar sprays [17, 19].…”
Section: Discussionmentioning
confidence: 99%
“…This strategy has the advantage of controlling CBB populations early in the growing season, which has been shown to be critical for minimizing crop damage for the remainder of the season [19]. This two-phase method will also help reduce pesticide inputs into the environment, as well as lower labor and production costs for the grower as pesticides will only need to be applied at certain points in the year rather than using regularly scheduled calendar sprays [17, 19]. A potential caveat to this may exist in that some coffee-growing regions experience year-round flowering and fruiting (e.g., Ka‘u on Hawai‘i Island), and this lack of a defined start to the coffee season may lead to difficulties in setting the start date for CBB development times using degree-days and the subsequent timing of pesticide sprays [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…comm.). A decision analysis conducted for CBB in Hawaii found that the initial infestation level was the most critical factor in maximizing the final net benefit of spraying B. bassiana [ 204 ]. Good pre- and early-season sanitation practices (e.g., strip-picking, pruning) work to keep infestation levels low throughout the growing season.…”
Section: Current State Of Cbb Management: Hawaii As a Case Studymentioning
confidence: 99%
“…A further drawback is that the chemicals are hazardous to farm workers and adversely affect biodiversity conservation, particularly natural enemies resulting in outbreaks of new pests 34 , 35 and contamination of water and soils 31 , but also pollinators potentially resulting in decreased fruit set 36 . Due to these drawbacks, it has been suggested that farmers should increase resources for field sanitation 37 . Biopesticides of fungal pathogens ( Beaveria bassiana and Metarhizium anisopliae ).…”
Section: Control Componentsmentioning
confidence: 99%